Lexicalisation and metaphorisation of Nigeria's unity in selected national newspapers' congratulatory announcements - Jibril, Ahmed Tanimu; Mohamad Ali, Afida; Mohd Kasim, Zalina; Chan, Mei Yuit (Routledge, 2021)
This study examines the linguistic resources employed in the discursive reproduction and normalisation of national unity, as constructed by the private sponsors of newspaper congratulatory announcements (NCAs) in Nigeria during the period between 2011 and 2016. The analysis is focused on how the processes of lexicalisation and metaphorisation were utilised in realising such discursive purposes. The study is theoretically informed bysystemic functional grammar (SFG) and theory of conceptual metaphors. The analysis includes linguistic analysis and qualitative content analysis (QCA) in identifying the lexical items as well as the figures of speech used in the NCAs. Findings from the analysis revealed that positively charged lexical items have been employed by the non-state sponsors of the NCAs in an attempt to recontextualise and normalise the unity discourse in the Nigerian context, which goes against the status quo and the lived experiences of the masses. Moreover, the problem of unity is also metaphorised, naturalised and reproduced in the NCAs in another attempt to transform and manipulate people’s thoughts and practices through such a metaphorical construction of unity.